Company information portal / Ng Sook Kei - Ng , Sook Kei (2003)
Company information Portal is a Web-based portal that provides related company information to users who visited the Web site It is developed to allow user readily and easily access a portal for information. With the Company Information Portal, user of Tenaga Nasional Berhad Generation (TNBG), Prai will be able to gather information of the company in the shortest period. The Company Information Portal is a combination or a few modules, namely company profile, projects for TNBG, TNBG site plan, statistical information and site map. The Prototyping model is chosen as the development methodology. Company information Portal is accomplished using technique suitable and compatible with a Windows 2000 operating system. ASP was used as the same main platform for development as together they made it possible to build a standard recognizable icons and user-friendly environment graphical user interface GUI). The user who has the administrator access right can be able to edit some of the information such as mission, vision, history and projects that can be changed from time to time. With this features, the user could easily update the latest changes without involving the coding.